Recognition and management of spinal cord injuries in sports and recreation - Tator, C. H. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Spinal injuries and spinal cord injuries in sports and recreation represent frequent and important causes of injury and disability. These injuries are virtually all preventable through strict adherence to the codes of conduct of the rules and regulations for sports and recreation and through an attitude of respect for one's own welfare and the welfare of the opponents or other participants. Adherence to guidelines for return to sport after injury can help to prevent worsening of deficits and the onset of new deficits.